The Useful of Social Media for Fish Floss Marketing on Dusun Babat Pasuruan Middle Business - Frigiyanto, Kharisma; Martinez, Lea; Febriana, Poppy (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The purpose of community service was to help the Fish Floss MSME how program promote the Fish Floss MSME product till this product becomes known by people and a prospective customer, starting, with promotion on social media where its social media created by this community service so it can grow trusted by prospective buyers who want to buy it product. Methodology: This community service activity goes through three stages, namely interviews and discussions, training and mentoring, and evaluation of the development of fish floss MSMEs. This form of training teaches how to photograph fish floss products to attract buyers' interest and helps create a business account on Instagram social media. Then the form of assistance provided to fish floss MSME owners is to see the progress of development in implementing social media and help evaluate the use of Instagram media. Results: Many people who will be prospective buyers know this fish floss is worth buying. Fish floss can be a complementary food for daily consumption because it contains many nutrients that humans need, and people know this fish floss has a nice taste. So not just a product, but really healthy and tasty. Through this community service program, the product is now reachable for many people to buy. Community service helps the Fish Floss MSME by making a social media promotion called Instagram. Applications/Originality/Value: This increase in community service research can be seen from fish floss MSME owners who do not yet understand how to market their products through online stores. Fish floss MSMEs still market their products in the form of regular WhatsApp stories and through word of mouth. So fish floss MSMEs, which previously did not have an Instagram account, now have one. By having 23 followers and 15 posts on an Instagram business account.